2021
DOI: 10.1093/bjsopen/zrab005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma progression during bridging before liver transplantation

Abstract: Background Recipient selection for liver transplantation in hepatocellular carcinoma (HCC) is based primarily on criteria affecting the chance of long-term success. Here, the relationship between pretransplant bridging therapy and long-term survival was investigated in a subgroup analysis of the SiLVER Study. Methods Response to bridging, as defined by comparison of imaging at the time of listing and post-transplant pathology… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The United Network of Organ Sharing (UNOS) guidelines suggest a downstaging protocol for patients beyond MC, focusing on their response to bridge therapy (41). Also, a recent study demonstrated that disease progression after bridging therapy is an independent risk factor for recurrence and mortality (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United Network of Organ Sharing (UNOS) guidelines suggest a downstaging protocol for patients beyond MC, focusing on their response to bridge therapy (41). Also, a recent study demonstrated that disease progression after bridging therapy is an independent risk factor for recurrence and mortality (42).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant data emerging from our multivariate analysis is the "protective role" of the minimally invasive approach. If patients develop RHCC much more time after the first IDLS, it is possible to experience longer tumor-free survival even after subsequent surgical treatments (42)(43)(44)(45)(46). The clinical entity of RHCC can be developed in different settings, and it depends on which first-line therapy was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Oligane et al [ 40 ] reported that the overall survival rate was higher, and the recurrence rate was lower in the BT group with T2 tumors that received MELD exceptions in a study using the UNOS database in the USA. Renner et al [ 41 ] from Germany reported that patients whose HCC progressed from within the Milan to outside the Milan criteria despite BT had lower overall survival and recurrence-free survival than those controlled within the Milan criteria. On the other hand, Ogawa et al [ 42 ] from Kyoto, Japan, reported that if LT was performed within the Kyoto criteria (≤10 lesions ≤5 cm, DCP ≤400 mAU/mL), results of LT were relatively good.…”
Section: Bridging Therapy To Liver Transplantationmentioning
confidence: 99%
“…Success rates for downstaging are acceptable and can be predicted by normalization of AFP levels prior to LT as well as wait times longer than 12 months [ 18 ]; recurrence rates after LT are satisfactory. However, tumor progression during waiting time for LT despite locoregional bridging appears to be an independent risk factor for increased recurrence and decreased outcome as shown in the SiLVER study [ 19 ]. Importantly, sufficiently long observation periods to identify favorable tumor biology need to be provided for successful LT outcomes [ 20 , 21 , 22 ].…”
Section: Transplantation For Cancermentioning
confidence: 99%